Antioxidant activity of proanthocyanidins-rich fractions from Choerospondias axillaris peels using a combination of chemical-based methods and cellular-based assay. (1st October 2016) - Li, Qian; Wang, Xieyi; Chen, Jun; Liu, Chengmei; Li, Ti; McClements, David Julian; Dai, Taotao; Liu, Jiyan
Highlights: Five fractions isolated from Choerospondias axillaris peels were studied. The fractions were rich in proanthocyanidins. Each fraction was characterized by HPLC to determine degree of polymerization. Antioxidant activity was analyzed by chemical and biological assays. Considerable differences were found between different antioxidant assays. Abstract: An extract isolated from Choerospondias axillaris peels was separated into five fractions using size-exclusion chromatography. The structural composition and mean degree of polymerization (mDP) of these fractions were then characterized by acid-catalysis followed by HPLC analysis. The antioxidant activity of each fraction was determined using a combination of chemical-based methods (DPPH, ABTS + radical scavenging activity, ferric-reducing antioxidant power, and phosphomolybdate assay) and a cellular-based assay. All fractions tested were found to have high total phenolics contents and were rich in proanthocyanidins. The mDP of fractions (F1–F5) ranged from 1.92 to 9.25. When tested by the chemical-based assays, the antioxidant activity of the fractions did not depend on molecular weight of the phenolics. Conversely, when tested by the cellular-based assay the antioxidant activity actually decreased with increasing molecular weight of the proanthocyanidins. These experiments highlight the limitations of using chemical-based assays to establish the antioxidant activity of proanthocyanidins within biological systems.